Quaternization of Composite Algal/PEI Beads for Enhanced Uranium Sorption—Application to Ore Acidic Leachate - Hamza, Mohammed F. (Gels, 2020)
The necessity to recover uranium from dilute solutions (for environmental/safety and resource management) is driving research towards developing new sorbents. This study focuses on the enhancement of U(VI) sorption properties of composite algal/Polyethylenimine beads through the quaternization of the support (by reaction with glycidyltrimethylammonium chloride). The sorbent is fully characterized by FTIR, XPS for confirming the contribution of protonated amine and quaternary ammonium groups on U(VI) binding (with possible contribution of hydroxyl and carboxyl groups, depending on the pH). The sorption properties are investigated in batch with reference to pH effect (optimum value: pH 4), uptake kinetics (equilibrium: 40 min) and sorption isotherms (maximum sorption capacity: 0.86 mmol U g(−1)). Metal desorption (with 0.5 M NaCl/0.5 M HCl) is highly efficient and the sorbent can be reused for five cycles with limited decrease in performance. The sorbent is successfully applied to the selective recovery of U(VI) from acidic leachate of uranium ore, after pre-treatment (cementation of copper, precipitation of rare earth elements with oxalate, and precipitation of iron). A pure yellow cake is obtained after precipitation of the eluate.